Aflatoxin M1 in raw milk in summer season in Lahore, Pakistan (Bangladesh Journal of Scientific and Industrial Research, 2024)
A four-month long study throughout the summer of 2022 i.e., April, May, June, and July; was conducted to determine Aflatoxin M1 concentration in raw milk retailed in the shops of Lahore, Pakistan. A total of 40 samples (10 per month) were analyzed using the ELISA kit method while considering European Union (50ng/kg), US Food and Drug Regulation Authority (500ng/kg), and Pakistan Pure Food Regulations (500ng/kg) as AFM1 permissible limits. About 82.50% of 40 samples were contaminated with AFM1 while only 17.50% samples were found to be uncontaminated. Of these contaminated samples over 87.88% samples exceeded the safe limit as set by the European Union i.e., 50ng/kg with only 12.12% of the samples being safe for use. On the other hand, only 6.06% of the samples were unfit as per the USFDA & Punjab Pure Food Regulations (PPFR) limit i.e., 500ng/kg. A mean value of 133.57 ± 0.14ng/kg of AFM1 contamination was calculated ranging from 5.43 ± 0.05ng/kg to 964.75 ± 0.04ng/kg in April and July, respectively. The lowest average contamination was recorded in May i.e., 68.35 ± 0.258ng/kg which went progressively higher in the later months due to unusual record-breaking rainfall in the region while highest average contamination was found in the month of July i.e., 228.789 ± 0.075ng/kg. The current study is significantly important as it identify the contamination of Aflatoxin M1 in raw milk in the summer season.Bangladesh J. Sci. Ind. Res. 59(2), 115-122, 2024